Metal-Organic Framework (MOF) derived Catalysts for Efficient Syngas Conversion to Oxygenates - Li, Fuping (Curtin University, 2020)
The direct synthesis of organic oxygenates from syngas has been widely reported during the past decade. Metal-organic frameworks (MOFs) have been considered as promising materials for their applications in the catalysis fields owing to the tunable porous structures and good configuration of active sites. In this project, Cu-, Zr- and Co-based MOF were applied as the platform to update these conventional catalysts with better performance for dimethyl ether and higher alcohols synthesis from syngas.